2020
DOI: 10.14744/dajpns.2019.00063
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Internet gaming disorder symptom severity with non-suicidal self-injury among young adults

Abstract: Objective: The aim of the present study was to evaluate the relationship of Internet gaming disorder (IGD) symptom severity with non-suicidal self-injury (NSSI) while controlling the effects of depression, anxiety and neuroticism among young adults. Method: The present study was conducted as a cross-sectional online self-report survey. The data were collected from 1010 volunteer Turkish university students in Ankara, persons who were in the e-mail database of a company located in Istanbul that organizes e-spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Mental health factors have a significant impact on adolescents’ pathological gaming [ 6 , 26 ]. Numerous studies have reported mental-related comorbidities in adolescents with pathological gaming, such as aggression [ 16 , 17 ], lack of self-control [ 5 , 16 ], major mental disorders such as depression and anxiety [ 10 , 27 , 28 ], ADHD [ 18 , 29 , 30 ], and so on. In particular, previous studies have indicated that time spent on violent games specifically might be associated with aggressive behavior [ 17 , 31 ].…”
Section: Pathological Gaming and Adolescents’ Mental Healthmentioning
confidence: 99%
“…Mental health factors have a significant impact on adolescents’ pathological gaming [ 6 , 26 ]. Numerous studies have reported mental-related comorbidities in adolescents with pathological gaming, such as aggression [ 16 , 17 ], lack of self-control [ 5 , 16 ], major mental disorders such as depression and anxiety [ 10 , 27 , 28 ], ADHD [ 18 , 29 , 30 ], and so on. In particular, previous studies have indicated that time spent on violent games specifically might be associated with aggressive behavior [ 17 , 31 ].…”
Section: Pathological Gaming and Adolescents’ Mental Healthmentioning
confidence: 99%
“…Recent studies have confirmed the association of Internet Gaming Disorder because of experiencing loneliness and overall impairment in functioning in young people's lives (Drageset et al, 2012;McHugh Power et al, 2018;Paulus et al, 2018). The authors consider the presence of experiencing loneliness measures as a measure of IGD symptom severity, with the personality trait of extraversion and low self-esteem accentuating the effect of the disorder (Danneel et al, 2017;Bodinger-deUriarte, 2019 Self-injurious and suicidal behaviors increase with increasing severity of Internet Gaming Disorder symptoms (Dalbudak, 2020;Bada, Clayton, 2020). Self-injurious behavior typically begins in adolescence and involves numerous episodes, and a variety of methods (Bada, Clayton, 2020), and represents the strongest predictor of suicide among adolescents (Zanus et al, 2021;Gainsbury, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…From the theoretical framework, IGD is positively associated with self-injurious and suicidal behavior (Yu et al, 2022;Guo et al, 2018;Dalbudak, 2020), and is also related to experiencing loneliness (Wang et al, 2022;Matalí et al, 2020;Ok, 2021). Depressive thoughts have been shown to accompany the experience of loneliness (Peerenboom et al, 2015), while also being closely linked to suicidal and selfinjurious behavior (Yu et al, 2022;Guo et al, 2018;Zanus et al, 2021).…”
Section: Introductionmentioning
confidence: 99%